The Impact of Macroeconomic Factors on IDX30 Stocks Through Profitability Period 2020-2024 - Nur Asti Wulandari; Zulfitra Zulfitra; Sri Retnaning Sampurnaningsih (Lafadz Jaya Publisher, 2025)
This research aims to examine and analyze the impact of inflation, interest rates, and the exchange rate of the rupiah on IDX 30 stocks through profitability during the 2020-2024 period. The type of research used is Descriptive Quantitative. The research population chosen as the object of this study is the Annual Financial Statements of companies included in the IDX30 index listed on the Indonesia Stock Exchange (BEI). The sample selection was conducted using the saturated sampling technique. The samples used include Inflation, Interest Rates, and the Exchange Rate of the Rupiah against Stock Prices with Profitability as the Intervening Variable in companies included in the IDX30 index listed on the Indonesia Stock Exchange (BEI). The research data was subsequently processed using Eviews 12 Software. The analysis method used is panel data regression, which is a combination of cross-section and time series data. The panel data regression analysis was conducted through model selection tests to determine the best model, and the test results indicate that the Fixed Effect Model (FEM) is the most appropriate model. The results of the coefficient of determination test against ROA show a value of 78.90%. The results of the coefficient of determination test against Stock Prices show a value of 89.41%. The hypothesis testing results indicate that Inflation and the Exchange Rate have a negative partial effect on ROA, Interest Rates do not affect the ROA variable, Inflation, Interest Rates, and the Exchange Rate simultaneously affect ROA, Inflation does not affect Stock Prices, Interest Rates, the Exchange Rate, and ROA have a partial effect on Stock Prices, Inflation, Interest Rates, and the Exchange Rate simultaneously affect Stock Prices.